Elevated RalA activity in the hippocampus of PI3Kγ knock-out mice lacking NMDAR-dependent long-term depression - Sim, Su-Eon (Korean Society for Biochemistry and Molecular Biology, 2013)
Phosphoinositide 3-kinases (PI3Ks) play key roles in synaptic plasticity and cognitive functions in the brain. We recently found that genetic deletion of PI3Kγ, the only known member of class IB PI3Ks, results in impaired N-methyl-(D)-aspartate receptor-dependent long-term depression (NMDAR-LTD) in the hippocampus. The activity of RalA, a small GTP-binding protein, increases following NMDAR-LTD inducing stimuli, and this increase in RalA activity is essential for inducing NMDAR-LTD. We found that RalA activity increased significantly in PI3Kγ knockout mice. Furthermore, NMDAR-LTDinducing stimuli did not increase RalA activity in PI3Kγ knockout mice. These results suggest that constitutively increased RalA activity occludes further increases in RalA activity during induction of LTD, causing impaired NMDARLTD. We propose that PI3Kγ regulates the activity of RalA, which is one of the molecular mechanisms inducing NMDARdependent LTD. [BMB Reports 2013; 46(2): 103-106]